Antenatally Diagnosed Hydronephrosis and Pelvi Ureteric Junction Obstruction from a Surgical Viewpoint - Govindarajan, Krishna Kumar (Journal of Pediatric Nephrology, 2020)
Background : Screening for anomalies in the antenatal period has resulted in a rapid surge in the identification of fetal hydronephrosis, which forms a formidable task for the treating physician. Summary: Pelvi-ureteric junction obstruction ranks the foremost among the children with antenatally diagnosed hydronephrosis. The dilemma of whether a dilated pelvicalyceal system is obstructed, and in need of surgical intervention to salvage from renal impairment, is a relevant point in the post-natal management of hydronephrosis detected antenatally. Key message: Majority of Hydronephrosis detected antenatally would require observation and the renal units identified to have obstruction need to be followed up with appropriate decision making on the need for surgery.